Ad-hoc, Mobile, and Wireless Networks : 14th International Conference, ADHOC-NOW 2015, Athens, Greece, June 29 -- July 1, 2015, Proceedings - Papavassiliou, Symeon; Ruehrup, Stefan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 14th International Conference on Ad Hoc Networks and Wireless, ADHOC-NOW 2015, held in Athens, Greece in June/July 2015. The 25 full papers presented in this volume were carefully reviewed and selected from 52 submissions. The book also contains 3 full-paper invited talks. The contributions are organized in topical sections named: routing, connectivity, and resource allocation; localization, sensor deployment, and mobility management; distributed computing with mobile agents; efficient, reliable, and secure smart energy networks; and emerging communications, networking and computing technologies for VANETs 2.0.
Routing, Connectivity, and Resource Allocation -- A Dynamic Topology Control Algorithm for Wireless Sensor Networks -- Geographic GReedy Routing with ACO Recovery Strategy GRACO -- Scheduling Connections via Path and Edge Multicoloring -- A Schedule Template Construction Technique for Duty Cycled Sensor Networks -- On the Impact of Network Evolution on NUM Resource Allocation Problems in Wireless Multihop Networks -- On the Problem of Resource Allocation and System Capacity Evaluation via a Blocking Queuing Model in D2D Enabled Overlay Cellular Networks -- Localization, Sensor Deployment, and Mobility Management Localization of a Mobile Node in Shaded Areas -- CAMS: Consensus-Based Anchor-Node Management Scheme for Train Localisation -- Delay Analysis of Context Aware Mobility Management Systems Addressing Multiple Connectivity Opportunities -- AdaMap: Adaptive Radiomap for Indoor Localization -- On the Displacement for Covering a Square with Randomly Placed Sensors -- Election-Based Sensor Deployment and Coverage Maintenance by a Team of Robots -- Distributed Computing with Mobile Agents Wireless Autonomous Robot Evacuation from Equilateral Triangles and Squares -- Rendezvous of Many Agents with Different Speeds in a Cycle -- The Random Bit Complexity of Mobile Robots Scattering -- On the Relations Between SINR Diagrams and Voronoi Diagrams -- Computations by Luminous Robots -- Online Lower Bounds and Offline Inapproximability in Optical Networks -- Efficient, Reliable, and Secure Smart Energy Networks A Modular and Flexible Network Architecture for Smart Grids -- A Linear Programming Approach for K-Resilient and Reliability-Aware Design of Large-Scale Industrial Networks -- Self-organised Key Management for the Smart Grid -- Information-Quality Based LV-Grid-Monitoring Framework and Its Application to Power-Quality Control -- Energy Efficient Small-Cell Discovery Using Users Mobility Prediction -- Emerging Communications, Networking and Computing Technologies for VANETs 2.0 Safety in Vehicular Networks on the Inevitability of Short-Range Directional Communications -- Secure Incentive-Based Architecture for Vehicular Cloud -- EYES: A Novel Overtaking Assistance System for Vehicular Networks -- Study of Probabilistic Worst Case Inter-Beacon Delays Under Realistic Vehicular Mobility Conditions -- xRadio: An Novel Software Defined Radio (SDR) Platform and Its Exemplar Application to Vehicle-to-Vehicle Communications.
Keywords: Computer Communication Networks; Telecommunication; Information Systems; Software engineering; Information storage and retrieva; Computer Communication Networks; Information Systems Applications (incl. Internet).; Communications Engineering, Networks; Management of Computing and Information Systems; Software Engineering; Information Storage and Retrieval